Aspirin Recapitulates Features of Caloric Restriction - Pietrocola, Federico (Cell Rep, 2018)
The age-associated deterioration in cellular and organismal functions associates with dysregulation of nutrient-sensing pathways and disabled autophagy. The reactivation of autophagic flux may prevent or ameliorate age-related metabolic dysfunctions. Non-toxic compounds endowed with the capacity to reduce the overall levels of protein acetylation and to induce autophagy have been categorized as caloric restriction mimetics (CRMs). Here, we show that aspirin or its active metabolite salicylate induce autophagy by virtue of their capacity to inhibit the acetyltransferase activity of EP300. While salicylate readily stimulates autophagic flux in control cells, it fails to further increase autophagy levels in EP300-deficient cells, as well as in cells in which endogenous EP300 has been replaced by salicylate-resistant EP300 mutants. Accordingly, the pro-autophagic activity of aspirin and salicylate on the nematode Caenorhabditis elegans is lost when the expression of the EP300 ortholog cpb-1 is reduced. Altogether, these findings identify aspirin as an evolutionary conserved CRM.